2013
DOI: 10.31436/iiumej.v14i1.315
|View full text |Cite
|
Sign up to set email alerts
|

Total Nitorgen Content from Earthworm (Eisenia Foetida) Using The Kjeldahl Method

Abstract: In the fish aquaculture management, fish feed is identified as a major problem. The high cost and scarcity of fishmeal in formulated feeds have led to the use of other protein sources such as earthworms and animal by-product. Earthworm is an alternative protein source to replace the fish meal in the fish feed formulation. In this study, total nitrogen content in earthworm powder is determined using the Kjeldahl method by employing the statistical software, Full Factorial Design (FFD) which could provide the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…For ages, earthworms have been utilized as agents of vermicomposting biotechnology to sustain soil fertility, reclaim wasteland, and treat organic wastes to a relatively less homogenous and desirable esthetic compound. The vermicomposting biotechnology takes advantage of the voracious, fast-growing, and reproduction nature of earthworms to convert organic waste to highly nutritious compounds [7,8].…”
Section: Vermitechnology VI S -à -Vi S Aquaculture Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ages, earthworms have been utilized as agents of vermicomposting biotechnology to sustain soil fertility, reclaim wasteland, and treat organic wastes to a relatively less homogenous and desirable esthetic compound. The vermicomposting biotechnology takes advantage of the voracious, fast-growing, and reproduction nature of earthworms to convert organic waste to highly nutritious compounds [7,8].…”
Section: Vermitechnology VI S -à -Vi S Aquaculture Nutritionmentioning
confidence: 99%
“…The vermicomposting products are earthworm biomass and vermiwastes: vermicompost (solid waste) and vermiliquid (liquid waste). The earthworm biomass is either fed directly to aquatic organisms or used as the protein source in formulating fish diets [7][8][9]. Nonetheless, the earthworms biomass utilization in fish feed production is limited by processing challenges (handling, harvesting, and gut content evacuation) and the presence of anti-nutritional factors (coelom fluid and chitin), which inhibit uptake, digestion, and assimilation by aquatic organisms [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The vermiliquid too can be utilized in formulating feed fish. Zhenjun et al (1997) (Kobayashi, Ohtomi, Sekizawa & Ohta, 2001;Mukti et al, 2012;Zakaria, Rahayu, MohdSalleh & Siti, 2013).…”
Section: Production Systems Of E Fetidamentioning
confidence: 99%
“…Most studies often use the Kjeldahl method to estimate the crude protein contents in E. fetida (Bou-Maroun et al, 2013;Chiu et al, 2015;De Chaves et al, 2015;Dynes, 2003;Gunya et al, 2016;Mohanta et al, 2016;Mukti et al, 2012;Rondón et al, 2003;Zhenjun et al, 1997). Zakaria et al (2013) involved the statistical software (full factorial design) to compare digestion time and the volume of acid (H 2 SO 4 ) using the Kjeldahl method. The authors suggested the worm sample to be digested for over 60 min in 15 ml H 2 SO 4 to produce the highest percentage levels of nitrogen contents in the worms.…”
Section: Processing Techniques For E Fetidamentioning
confidence: 99%
See 1 more Smart Citation